MYSIR’s Abstracts 1: Annual Scientific Meeting 2023 - Malaysian Society of Interventional Radiology (The Interventionalist Journal, 2023)
MYSIR’s Abstracts 1 1. OP01: ENDOVASCULAR MANAGEMENT OF IATROGENIC BRACHIOCEPHALIC ARTERY INJURY USING BALLOON TAMPONADE 2. OP02: The Effect of Eye Heights on the Entrance Surface Doses (ESD) of Skull Phantoms at the Radiologist and Nurse Locations in PTBD Procedure 3. OP03: FISH BONE INJURY CAUSING TRAUMATIC ARTERIOVENOUS FISTULA, SUCCESSFULLY TREATED WITH EMBOLIZATION 4. OP04: A 5 YEAR RETROSPECTIVE STUDY OF POST TRANSARTERIAL EMBOLIZATION FOR GASTROINTESTINAL BLEED IN UNIVERSITY MALAYA MEDICAL CENTRE, MALAYSIA 5. OP05: Outcomes of Bleomycin Sclerotherapy In The Treatment Of Venous Malformations - A Single Centre Case Series 6. OP06: Findings from using catheter venography and cone-beam CT to investigate for Pelvic Venous Congestion Syndrome